Vital Statistics on Congress 2008 - Ornstein, Norman J. (Book collections on Project MUSE., 2008)
Vital Statistics on Congress remains the quintessential source of authoritative information on America's legislature. This important series tracks the elements that define and describe Congress in the post-World War II era, and in this new edition, three of America's most esteemed political analysts extend their examination through the 109th Congress. They combine historical context with insightful analysis and copious data to produce a valuable and authoritative picture of the U.S. Senate and House of Representatives. Norman Ornstein, Thomas Mann, and Michael Malbin track the changing makeup of Congress through history and across several dimensions, such as region, party, occupation, religion, committee assignments, staff size, and political stances. They document trends in critical areas such as voter turnout, ticket splitting, incumbency and turnover, and margin of victory. The authors, acknowledged experts in campaign finance, provide detailed information on candidate, party, and PAC spending. The material presented in l Statistics on Congress 2008 rev reveals a fascinating and important picture of America's chosen representatives, as politicians and as people. It will be an important addition to the bookshelves of media, political professionals, scholars and their students, and political junkies everywhere.